SABUN EKSTRAK MANGKOKAN (Nothopanax ScutellaiumMerr) SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus aureus - Galuh Ratmana Hanum; Syahrul Ardiansyah (FMIPA : Universitas PGRI Adi Buana, 2017)
The soap of mangkokan (Nothopanax Scuteliaium Merr) leaf extract is a soap made from extracts of leaves mangkokan (Nothopanax Scuteliaium Merr) with different concentration of mangkokan leaf extract, among others, 70%, 80% and 90%. The Purpose of this research to determine the effect of concentration of mangkokan soap on the physical properties and microbiology. Physical properties include pH and water content while Microbiology includes the inhibitation of the bacterium Staphylococcus aureus. Analysis in this reasearch using one way anova factorial design 1 x 3. The results obtained in this reasearch is the difference in concentration of mangkokan (Nothopanax Scuteliaium Merr) leaf extract significantly affect the pH value of the soap and the difference in concentration of mangkokan (Nothopanax Scuteliaium Merr) leaf extract there is no significant influence on the water content and the inhibition of bacterial. Keywords : Soap, Leaves Mangkokan, Staphylococcus aureus.